From Facilitator to Activator: Evaluating Teaching Professional Practice in the Integration of Differentiated Instruction and Deep Learning - Casmudi Casmudi; Ririn Suyanti (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
The integration of Differentiated Instruction (DI) and Deep Learning (DL) is crucial for building 21st-century (4C) skills, yet teachers are frequently constrained in mapping student characteristics and face the psychological pressure of curriculum transition. This study aims to analyze the implementation of DI-DL integration and the factors influencing its effectiveness at the junior secondary (SMP) level. Using an explanatory sequential mixed-methods design (QUAN-Qual), the study involved 35 teachers and 81 students. Quantitative survey data were collected through a peer-validated questionnaire in the curriculum field and analyzed using descriptive statistics. Qualitative data were gathered through semi-structured interviews involving 12 key informants (teachers and students), analyzed using QDA Miner in the coding process. The quantitative results show a dominance of visual learners (51.9%). DI-DL integration was shown to significantly improve social-interactive competencies, namely collaboration (M = 15.2) and communication (M = 14.0), but was less optimal for higher-order cognitive skills, particularly creativity (M = 4.8). The qualitative findings reveal that systemic inertia caused by the rigidity of the Minimum Mastery Criteria (KKM) and teachers' cognitive overload triggers instructional fragmentation that hinders deep intellectual growth. The study concludes that DI-DL integration currently remains a fragile innovation. Systemic policy reform and explicit cognitive scaffolding are needed to transform social participation into students' original innovation.